Tunnel Infection and Peritonitis Induced by Staphylococcus aureus Due to Decubitus Change of the Anterior Abdominal Wall in a Patient on Peritoneal Dialysis: Case Report - Marko Baralić; Ana Bontić; Jelena Pavlović; Vidna Karadžić-Ristanović; Selena Gajić; Jovan Jevtić; Pavle Popović; Kristina Petrović; Lara Hadži-Tanović; Aleksandra Kezić (Microorganisms)
The occurrence of anterior abdominal wall ulcer at the site of the peritoneal catheter (PC) is one of the rarest complications of peritoneal dialysis (PD). When present, it is mainly caused by staphylococci which respond well to vancomycin therapy. Despite well-conducted therapy, there is a tendency to relapse and induce peritonitis, which makes it necessary to remove the PC and change the dialysis model of treatment and/or re-insert the catheter at another place to preserve PD as a treatment method. In the present study, we discuss a case of a 53-year-old patient with end-stage kidney disease treated with PD and with decubitus changes at the PC exit site; the change occurred due to migration of the catheter middle part by protruding from the abdominal cavity to the skin, thus allowing ulcer appearance. Although the PC site was treated with antibiotics, as advised by the surgeon, the patient was finally transferred to hemodialysis as the repositioning of the catheter was not performed. This leads to the conclusion that the antibiotic treatment and catheter repositioning are mandatory to preserve peritoneal dialysis as an end-stage kidney disease (ESKD) treatment model.